2014
DOI: 10.1017/s0950268813003361
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin polymorphisms and the risk of sepsis: evidence from a meta-analysis

Abstract: Several studies have evaluated the association between mannose-binding lectin (MBL) polymorphisms and sepsis. However, the results are inconclusive and conflicting. To better understand the roles of MBL polymorphisms in sepsis, we conducted a comprehensive meta-analysis. All relevant studies were searched from PubMed, EMBASE and Web of Knowledge databases, with the last report up to 7 May 2013. Twenty-nine studies addressing four MBL polymorphisms (-550G/C, -221G/C, structure variant A/O, Gly54Asp) were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Nevertheless, there was no suggestion of an effect on the incidence of posttransplant infection either in the recessive or dominant modeling. This apparent lack of impact for promoter SNPs is concordant with other meta‐analyses focused on the risk of sepsis, tuberculosis, or progression/chronicity of hepatitis B virus infection in nontransplant populations.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Nevertheless, there was no suggestion of an effect on the incidence of posttransplant infection either in the recessive or dominant modeling. This apparent lack of impact for promoter SNPs is concordant with other meta‐analyses focused on the risk of sepsis, tuberculosis, or progression/chronicity of hepatitis B virus infection in nontransplant populations.…”
Section: Discussionsupporting
confidence: 84%
“…The existence of a network of redundant mechanisms and both soluble and membrane‐bound receptors involved in the recognition of pathogen‐associated molecular patterns may contribute to partially dilute the detrimental effect attributable to impaired MBL production . Interestingly, the absolute values of these RRs were in line with those estimated in the general population for the development of sepsis among carriers of variant alleles of exon 1 SNPs …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Studies have found that low serum MBL, usually caused by gene variation, has been related to more frequent and severe infections (6)(7)(8)(9). The associations between MBL2 gene polymorphisms, circulating MBL levels, and susceptibility and out- comes in sepsis have been reported in several studies but have shown conflicting results (10)(11)(12)(13). Moreover, the concentrations of MBL may be diverse in patients with different ethnicities and ages (14).…”
Section: Introductionmentioning
confidence: 99%